Metode Pembelajaran di SMP Mamba’us Sholihin Berbasis Pondok Pesantren - Shelfiya Anjani (STIKes Ibnu Sina Ajibarang, 2024)
Mamba'us Sholihin Middle School is a school that is under the same foundation as the Mamba'us Sholihin Islamic boarding school. The purpose of writing this article is to find out what learning methods are used at Mamba'us Sholihin Blitar Middle School. This research is qualitative research, in which in this research, the author conducted a literature review and interviews to obtain the data. In the learning process, teachers use lecture methods, memorization, and also singing or what is usually called lalaran. The lecture method is a method of verbal explanation and narrative carried out by the teacher in front of the class. The memorization method is a method that can retain the learning material that students have learned. The recitation method is a rote repetition activity carried out individually or in groups using the desired rhythm.